Formulasi Emulgel Masker Wajah Ekstrak Ubi Jalar Ungu (Ipomoea Batatas Var. Ayamurasaki) dengan Uji pH, Homogenitas, dan Aktivitas Antioksidan - Kurniaty, Ika; Nugrahani, Ratri Ariatmi; Hasyim, Ummul Habibah; Sari, Fatma; Nurfida, Anita; Syafira, Izzatus (SURYA TEKNIKA, 2026)
The utilization of purple sweet potato (Ipomoea batatas var. Ayamurasaki) as a natural antioxidant agent in emulgel cosmetic formulations offers potential for developing effective facial skincare products. The anthocyanin pigments contained in purple sweet potato were extracted via the reflux method using 70% ethanol, yielding a 13% extract. The total anthocyanin content was measured at 26.72 mg/100g wet weight, providing potent antioxidant activity with an IC₅₀ value of 10.77 ppm. Various extract concentrations (F1–F6) incorporated into the emulgel base demonstrated physical characteristics that met cosmetic standards, including excellent homogeneity and a stable pH range between 5.3 and 6.8. The evaluation of antioxidant activity revealed a positive correlation between increasing extract concentration and the effectiveness of free radical scavenging. Formula F6 yielded the most optimal antioxidant activity with an IC₅₀ value of 8.39 ppm. These emulgel face mask preparations proved to be physically stable and possess significant skin protection potential against oxidative stress. Purple sweet potato is verified as a viable natural active ingredient for topical product formulation, providing functional added value for the development of nature-based cosmetics.